Conditioned medium of IGF-1-induced human synovial membrane mesenchymal stem cells effects on inflammatory response of osteoarthritic in vitro model - Marlina, Marlina; Armenia, Armenia; Rahmadian, Rizki; Widodo, Wahyu Setia; Haddeline, Syarifah Fadhlira; Safitri, Maharani; Elida, Nur; Widowati, Wahyu (Life Sciences, Medicine and Biomedicine, 2023)
Synovial membrane mesenchymal stem cells (SM-MSCs) possess excellent regenerative potential, making them a viable option for osteoarthritis (OA) therapy. Moreover, these cells can be easily obtained from the human body.  Insulin-like growth factor (IGF-1) can be used to decrease the pro-inflammatory marker, these markers can trigger inflammation in OA. These challenges can be addressed by utilizing a conditioned medium (CM) derived from stem cell culture. This study aims to compare the effective way of OA therapy between CM SM-MSC and CM SM-MSC induced by IGF-1 by observe the pro-inflammatory markers such as NF-kB, RANTES, PGE2, COL1 and the anti-inflammatory marker, Aggrecan (ACAN). Chondrocyte cells induced IL-1β as OA model (IL1β-CHON002) treated with IGF-1 15% and 30% and without IGF1-induced SM-MSCs-CM to know its effectiveness in decreasing the pro-inflammatory markers. ELISA and RT-qPCR methods were performed to analyze this effect. Based on the data result, SM-MSCs-CM is estimated to have the potential to treat OA as seen from the content of growth factors in CM, decreasing the markers of inflammation. The most significant reduction in PGE2, RANTES, NF-kB, and COL1 concentration was found in the treatment of SM-MSCs-CM cultured with IGF1 concentrations of 150 ng/mL. The higher aggrecan (ACAN) concentration was found in IGF150 15%. Conclusion: CM from SM-MSCs cultured with IGF150 with concentrations of 15% and 30% resulted in the most effective concentration to decrease the concentration of pro-inflammatory markers and also to increase the anti-inflammatory markers.